False equivalence? Differences in the post-16 qualifications market and outcomes in higher education. Issue 2 (15th March 2018) - Shields, Robin; Masardo, Alexander
Abstract: This paper investigates differences in higher education outcomes according to the qualifications with which students enter university. The study is situated in the context of increasing marketization, competition and privatization in post-16 qualifications, combined with an increase in students entering higher education with either vocational qualifications (e.g. the Business and Technology Education Council [BTEC] qualification) or a mix of academic and vocational qualifications. It draws upon literature on markets in education as well as studies on educational choice and pathways to examine whether different entry qualifications offer equal chances of success in higher education. Using multilevel logistic regression, the analysis examines the relationship between types of entry qualifications (academic, vocational and mixed) and the probability of achieving a first or upper-second class degree at university, which are associated with increased opportunities in the labour market and postgraduate study. Controlling for a range of demographic and institutional characteristics, the analysis identifies a strong decrease in the probability of a first or upper-second class degree for students who enter higher education with vocational qualifications. These results are discussed in relation to theories of markets in education and social class and education